2023
DOI: 10.3390/su152416641
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Ecological Risk Assessment and Spatial Pattern Evolution Analysis of the Central Yunnan Urban Agglomeration from 1995 to 2020 Based on Land Use/Cover Change

Ruifang Deng,
Xue Ding,
Jinliang Wang

Abstract: The central Yunnan urban agglomeration represents a typical urban cluster in the southwestern region of China. The swift urbanization and land use changes in this region pose a severe threat to the ecosystem. A thorough assessment of the landscape ecological risk in the central Yunnan urban agglomeration holds paramount importance for devising effective risk management strategies and sustainable, high-quality development plans. This study utilizes long-term land-use raster data for six time periods (1995, 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…With the rapid development of global industrialization and economic levels, the demand for mineral resources is rising, and the large-scale exploitation of mineral resources has a large impact on the use of land resources and the ecological environment [1]. Studies have shown that ecosystem stability and ecological risk assessment are more significantly affected by land use change [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the rapid development of global industrialization and economic levels, the demand for mineral resources is rising, and the large-scale exploitation of mineral resources has a large impact on the use of land resources and the ecological environment [1]. Studies have shown that ecosystem stability and ecological risk assessment are more significantly affected by land use change [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the classification methods of mine features based on satellite remote sensing images mainly include visual interpretation and supervised classification [5]. There are two main problems: (1) Visual interpretation has a high level of accuracy, but the workload is large, and the interpretations by personnel are subjective. Knowledge has a greater impact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid urbanization process and constantly expanding urban population have brought many problems related to the sustainable utilization of resources, such as land resource scarcity and urban traffic congestion throughout the world [1,2], which has resulted in a sharp increase in the required utilization of urban underground space [3,4]. As a result, an unprecedented scale of underground space engineering construction has been implemented alongside the accelerated urbanization process in recent years [5].…”
Section: Introductionmentioning
confidence: 99%